METHODS OF TEACHING ENGLISH FOR SPECIFIC PURPOSES - Dadabayev Zafar Zakirovich (Journals Park Publishing, 2025)
This article analyzes modern competencies in teaching English to chemistry students. An integrative approach plays an important role in developing chemistry students’ English reading competence. It also discusses the model for improving the integrative methodology of language teaching.
Keywords: Teaching, methodology, competency, integrative approach, task, creative thinking.